Open source cable models for EMI simulations - Greedy, Steve; Smartt, C.; Thomas, David W.P. (2016)
This paper describes the progress of work towards an Open Source software toolset suitable for developing Spice based multi-conductor cable models. The issues related to creating a transmission line model for implementation in Spice which include the frequency dependent properties of real cables are presented and the viability of spice cable models is demonstrated through application to a three conductor crosstalk model. Development of the techniques to include models of shielded cables and incident field excitation has been demonstrated.